Expectancy violation, reduction of food cue reactivity and less eating in the absence of hunger after one food cue exposure session for overweight and obese women. (January 2016) - Schyns, Ghislaine; Roefs, Anne; Mulkens, Sandra; Jansen, Anita
Abstract: The present study investigated whether a single-session of food cue exposure for overweight women would decrease 'if CS then US' expectancies, cue reactivity and eating in the absence of hunger (EAH). EAH was measured in a behavioural paradigm that enabled to also investigate whether the cue exposure effects were specific for exposed foods or would generalise to food items that were not present during exposure. Overweight women were randomly assigned to either the cue exposure intervention or a control intervention that focused on body image. In line with the hypotheses, results showed that cue exposure induced a significant decrease in 'if CS then US' expectancies, in contrast to the control intervention. It was also found that, compared to the control intervention, desires to eat initially increased during cue exposure while gradual extinction was observed towards the end of the intervention. No extinction of increased salivation responses was found. Regarding EAH, the intake of the exposed food item was significantly less in the exposure condition than in the control condition, whereas total caloric food intake was not different between conditions, indicating that cue exposure was effective in reducing intake but did not generalise to the intake of other food items. Highlights: One cue exposure session was compared to a control intervention in overweight women. Cue exposure led to a decrease in 'if CS then US' expectancies. Cue exposure initially increased cue reactivity (salivation & desire to eat). Extinction of desire to eat was found at the end of the cue exposure intervention. Cue exposure led to less eating in the absence of hunger of the exposed food item.